Oralidade dos alunos do ensino médio do CAFS: um estudo de caso - Araújo, Edmilsa Santana de (2005)
The research is case's study. The study analyzes the orality of students ofthe Campus Amílcar Ferreira Sobral - CAFS in Floriano, Piauí. It presents the ligüísticas trespasses, diversities, similarities and meaning that characterize the speeches of those students. A bibliographical revision on verbal language and its relation with the education, and language as social participation was carried. The subjects were 30 pupils of the CAFS, divided in 3 groups of 10 in accordance with the series where they are registered. They had attended televising fílms and news, had heard stories, cases, musics, and songs. After that experience they were asked to verbally reproduced their impressions in a recorded individual interview. The results ofthe inquiry indicate that the pupils do not demonstrate good performance in its speeches. The linguistic problems found were: narratives with improper sequence ofthe facts, vices of language, inadequate agreement, and conversational markers. One concludes that the pupils use more the restricted code that the elaborated.